PENGGUNAAN METODE PEMBELAJARAN SING A SONG UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SDN KAUMAN II: THE USE OF SING A SONG LEARNING METHOD TO IMPROVE THE LEARNING OUTCOMES OF CLASS IV STUDENTS OF KAUMAN II ELEMENTARY SCHOOL - Kusuma, Eka Maya; Setyawan, Agung (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
Learning learning methods, which serve as tools to achieve educational goals, is very important. Despite the availability of various approaches, teachers often rely on lectures as their main method. This research examines the impact of the Nyanyi Lagu method on student learning outcomes. As an interactive approach, Nyanyikan Lagu actively involves students in the learning process. Conducted as a classroom action research using the Kemmis and McTaggart model, this study involved 22 fourth grade students of SDN Kauman II. Data was collected through multiple choice tests, observations, and interviews. Before using Nyanyi Lagu, the students' average score was 69.55. This increased to 76.36 in the first cycle and 84.09 in the second cycle, with success rates of 59.09% and 81.81% respectively. This method effectively improved learning outcomes by 22.72%. Although Nyanyikan Lagu is suitable for elementary school, its implementation should be supported with interesting media to maintain students' interest.